Optimal control with disturbance estimation - Dušek, František; Honc, Daniel; Kizhakke Illom, Rahul Sharma (Nottingham Trent University, 2017)
The paper deals with a very common situation in many control systems and this is the fact that, for zero control action, the controlled variable is nonzero. This is often caused by the existence of another process input which is uncontrolled. Classic controllers do not take into account the second input, so deviation variables are considered or some feedforward controller is used to compensate the variable. The authors propose a solution, that the process is considered as a system with two inputs and single output (TISO). Here, the uncontrolled input is estimated with the state observer and the controller is designed as the multivariable controller. A Linear-quadratic (LQ) state-feedback control and model predictive control (MPC) of simple thermal process simulations are provided to demonstrate the proposed control strategy.
Optimální řízení s odhadem poruchy
Keywords: Control; optimal control; LQ controller; model predictive control; disturbance; estimation; thermal process; řízení; optimální řízení; LQ regulátor; prediktivní řízení; porucha; odhad; tepelný systém